Involvement of β3-adrenergic receptors in the control of food intake in rats - Kanzler,S.A. (2011)
This study examined the food intake changes evoked by intracerebroventricular (icv) injection of a selective agonist (BRL37344, 2 and 20 nmol) or antagonist (SR59230A, 10 and 50 nmol) of β3-adrenergic receptors in 24-h fasted rats (adult male Wistar rats, 200-350 g, N = 6/treatment). The animals were also pretreated with saline icv (SAL) or SR59230A (50 nmol) followed by BRL37344 (20 nmol) or SAL in order to determine the selectivity of the effects evoked by BRL37344 on food intake or the selectivity of the effects evoked by SR59230A on risk assessment (RA) behavior. The highest dose of BRL37344 (N = 7) decreased food intake 1 h after the treatment (6.4 ± 0.5 g in SAL-treated vs 4.2 ± 0.8 g in drug-treated rats). While both doses of SR59230A failed to affect food intake (5.1 ± 1.1 g for 10 nmol and 6.0 ± 1.8 g for 50 nmol), this treatment reduced the RA frequency (number/30 min) (4 ± 2 for SAL-treated vs 1 ± 1 for 10 nmol and 0.5 ± 1 for 50 nmol SR59230A-treated rats), an ethological parameter related to anxiety. While pretreatment with SR59230A (7.0 ± 0.5 g) abolished the hypophagia induced by BRL37344 (3.6 ± 0.9 g), BRL37344 suppressed the reduction in RA frequency caused by SR59230A. These results show that the hypophagia caused by BRL37344 is selectively mediated by β3-adrenergic receptors within the central nervous system. Moreover, they suggest the involvement of these receptors in the control of anxiety.